THE ROLE OF LINGUOCULTUROLOGY IN ENGLISH, UZBEK LINGUISTICS AND THE FORMATION OF MODERN RESEARCH IN THE FIELD - Sodiqova, Sayyoraxon (QO‘QON UNIVERSITETI XABARNOMASI, 2025)
This study explores the role of linguoculturology in English and Uzbek linguistics, highlighting how cultural values, historical experiences, and societal norms shape language structures and communication styles. Through a comparative analysis of lexical items, idioms, humor styles, and conceptual metaphors, the study demonstrates the deep interconnection between language and culture. Findings indicate that English, rooted in individualism, frequently employs business and efficiency-related metaphors, while Uzbek, shaped by collectivism, relies on nature and social harmony in its expressions. The research underscores the importance of linguocultural awareness in language education, translation, and intercultural communication. The study concludes that linguoculturology is essential for understanding linguistic diversity and improving cross-cultural interactions.